Hubungan Motivasi Dengan Self-Care Management pada Lansia Hipertensi di Puskesmas Tengaran: The Relationship Between Motivation and Self-Care Management in Elderly with Hypertension at Tengaran Community Health Center - Yulia Eka Ariani; Suwanti (Journal of Holistics and Health Sciences, 2026)
Hypertension is a chronic disease commonly experienced by the elderly and requires continuous management through self-care management to prevent complications. However, the implementation of self-care management among the elderly is often not optimal. Motivation is an internal factor that plays an important role in encouraging elderly individuals to consistently engage in self-care behaviors. This study aimed to analyze the relationship between motivation and self-care management among elderly with hypertension at Tengaran Primary Health Center. This study employed a quantitative design with a cross-sectional approach. The population consisted of 79 elderly individuals with hypertension, and all participants were included as samples using a total sampling technique. Data were collected using the HBP-SCP Motivation Scale and HBP-SCP Behaviour Scale questionnaires. Data analysis was conducted using Spearman Rank correlation test. The results showed that most elderly participants had moderate motivation (58 respondents; 73.4%) and moderate self-care management (63 respondents; 79.7%). Spearman Rank test show (p-value = 0.000 <0,05; r = 0.422) indicated positive and moderate strenght relationship between motivation and self-care management, indicated  a positive correlation with moderate strength.There is a significant relationship between motivation and self-care management among elderly with hypertension at Tengaran Primary Health Center. Therefore, improving motivation in elderly with hypertension is necessary use micro-habit approach.   ABSTRAK Hipertensi merupakan penyakit kronis yang banyak dialami lansia dan memerlukan pengelolaan berkelanjutan melalui self-care management untuk mencegah komplikasi. Namun, pelaksanaan self-care management pada lansia sering belum optimal. Motivasi merupakan faktor internal yang berperan penting dalam mendorong keterlibatan lansia dalam menjalankan perawatan diri secara konsisten. Penelitian bertujuan untuk menganalisis hubungan motivasi terhadap self-care management pada lansia dengan hipertensi di Puskesmas Tengaran Penelitian ini adalah kuantitatif dengan pendekatan cross-sectional. Populasi dalam penelitian ini berjumlah 79 lansia dengan hipertensi, dan seluruh populasi dijadikan sampel menggunakan teknik total sampling. Pengumpulan data menggunakan kuesioner HBP-SCP Motivation Scale dan HBP-SCP Behaviour Scale. Analisis data dilakukan menggunakan uji korelasi Spearman Rank. Hasil penelitian menunjukkan sebagian besar lansia memiliki tingkat motivasi pada kategori sedang sebanyak 58 responden (73,4%) dan self-care management juga pada kategori sedang sebanyak 63 responden (79,7%). Hasil uji spearman rank menunjukkan (p-value = 0,000 < 0,05 dan r= 0,422) untuk hubungan yang positif dengan kekuatan sedang antara motivasi dengan self-care management pada lansia dengan hipertensi di Puskesmas Tengaran. Terdapat hubungan yang signifikan atara motivasi dan self-care management pada lansia hipertensi di Puskesmas Tengaran. Oleh karena itu meningkatkan motivasi pada lansia dengan hipertensi perlu dilakukan dengan cara pendekatan kecil tapi konsisten (micro-habits)